Analisis Potensi Tanah Longsor Di Kecamatan Dlingo, Kabupaten Bantul Menggunakan Sistem Informasi Geografis (SIG) Tahun 2016 - Nalunggara, Atsari, Dr. Ir. Imam Hardjono, M.Si (2017)
Landslides are a displacement or land mass movements are caused by the soil no longer strong enough to bear the weight that was on the ground. Landslides also influenced by several variables such as, slope, rainfall, land use, soil type, and geological factors. Dlingo is one of district in Bantul Regency that has a high percentage of landslide occurrences. Therefore, as a first step to overcome the disaster, the needed analysis of the distribution of the level of danger of landslides and analyze the dominant factors that affect the level of landslide potential. The method used in this research of landslide potential is survey method. Survey method consists of the method of data collection, data processing method, and data analysis methods. Analysis of the data including quantitative tiered GIS analysis. The method used in the determination of the sample is purposive sampling. The results of GIS analysis shows that the high level of landslide potential is in the eastern part of the District Dlingo. The level of danger of landslides were scattered throughout the District Dlingo village. Low landslide potential level is in the northern part. The dominant factor affecting the level of landslide hazard is rainfall and geology.